Using Forum Theatre to mobilise knowledge and improve NHS care: the Enhancing Post-injury Psychological Intervention and Care (EPPIC) study. (9th May 2022) - Beckett, Kate; Deave, Toity; McBride, Tony; le May, Andrée; Gabbay, John; Kapoulas, Urszula; Long, Adele; Warburton, Georgie; Wogan, Celia; Cox, Lee; Thompson, Julian; Spencer, Frank; et al.
Abstract : Background: Evidence regarding the impact of psychological problems on recovery from injury has limited influence on practice. Mindlines show effective practice requires diverse knowledge which is generally socially transmitted. Aims and objectives: Develop and test a method blending patient, practitioner, and research evidence and using Forum Theatre to enable key stakeholders to interact with it. Assess this methods; impact on contributing individuals/groups; on behaviour, practice, and research; mechanisms enabling these changes to occur. Methods: Stage-1: captured patient (n=53), practitioner (n=62), and research/expert (n=3) evidence using interviews, focus groups, literature review; combined these strands using framework analysis and conveyed them in a play. Stage-2: patients (n=32), carers (n=3), practitioners (n=31), and researchers (n=16) attended Forum Theatre workshops where they shared experiences, watched the play, re-enacted elements, and co-produced service improvements. Stage-3: used the Social Impact Framework to analyse study outcome data and establish what changed, how and why. Findings: This approach enhanced individuals'/group knowledge of post-injury psychopathology, confidence in their knowledge, mutual understanding, creativity, attitudes towards knowledge mobilisation, and research. These cognitive, attitudinal, and relational impacts led to multilevel changes in behaviour, practice, and research. Four key mechanisms enabled this research to occur and create impact: diverse knowledge, drama/storytelling, social interaction, actively altering outcomes. Discussion and conclusions: Discourse about poor uptake of scientific evidence focuses on methods to aid translation and implementation; this study shows how mindlines can reframe this 'problem' and inform impactful research. EPPIC demonstrated how productive interaction between diverse stakeholders using creative means bridges gaps between evidence, knowledge, and action.